Análisis de las prácticas evaluativas desde la perspectiva de los propios actores y actoras en la Región Atlántica - Badilla Chavarría, Leda (2005)
The purpose of the investigation was to evaluate from a qualitive perspective the Scholastic Evaluation component in the project conducted in the Atlantic area of the country involved different participants of the educational community: regional teams, advisors, educators, parents, students. Diverse techniques were used to complete the information. The analysis departs from the logical experiences of the actors in the evaluative process. Problems and solutions were also identified by the participants. Because of the characteristics of the study the voices of the participants are included. The texts are presented the way they were expressed by the actors.